Power generation overcapacity in selected sub-Saharan African countries: political-economic drivers and grid infrastructure challenges - Ndayishimiye, Vedaste; Bakkabulindi, Geofrey; Miyingo, Emmanuel Wokulira; Nibagwire, Deborah (Frontiers in Energy Research, 2025)
Sub-Saharan Africa (SSA) faces a persistent energy crisis, with 600 million people lacking access to electricity. Since the 1990s, government-led reforms have facilitated Independent Power Producers (IPPs) in adding 29.3 GW from 371 projects between 2000 and 2024. However, by 2018, inadequate grid investment had led to overcapacity in some countries while millions remained without electricity, creating a paradox. This study examined the role of political economy, the IPP model, the funding gap in transmission and grid extension, and the impact of renewable energy project development on overcapacity in the power generation sector of SSA. The analysis was based on data from international organizations involved in energy and economic development, national energy plans and reports, and both primary and secondary research. Case studies from Ghana, South Africa, and Ethiopia were selected due to documented overcapacity challenges. The findings revealed that political influence, misaligned investments, and weak grid infrastructure are key contributing factors to overcapacity. Between 2001 and 2023, 97% of private investment was directed towards generation, while only 0.2% supported transmission expansion, leaving grids underfunded. Additionally, 43% of generation projects were awarded through direct negotiations and confidential agreements, resulting in inefficiencies and inflated costs. Take-or-pay Power Purchase Agreements have further exacerbated excess capacity, while transmission delays and weak regional interconnections continue to keep much of the capacity underutilized. Given these points, overcapacity in SSA’s power generation sector is a result of politically driven investments that overlook demand and grid capacity requirements leading to inefficiencies and financial strain. To address this challenge, governments should increase grid expansion investments, enhance regulatory transparency, reform procurement and strengthen regional electricity trade.